When It Comes to Container Port Efficiency, Are All Developing Regions Equal? - Ancor Suárez-Alemán; Javier Morales Sarriera; Tomás Serebrisky; Lourdes Trujillo (Inter-American Development Bank (IDB), 2015)
This paper develops a port productivity and efficiency analysis of all developing regions between 2000 and 2010, using both parametric and nonparametric approaches. From a unique dataset -our sample covers 70 developing countries, 203 ports, and 1,750 data points-, we carry out an analysis of the evolution and drivers of productivity and efficiency changes across developing regions. We show that productivity growth rates between 2000 and 2010 vary significantly and that this heterogeneity is explained by pure efficiency changes rather than scale efficiency of technological changes. Therefore, we carry out a detailed efficiency analysis to determine the drivers of port efficiency. Time series results show an upward trend for port efficiency in developing regions, as it increased from 47 percent in 2000 to 57 percent in 2010. Our analysis indicates that private sector participation, the reduction of corruption in the public sector and improvements in liner connectivity and the existence of multimodal links increase the level of port efficiency in developing regions.
hdl:11319/6788
Keywords: L51; L91; L92; O18; 330; productivity; technical efficiency; ports; developing regions; benchmarking